CLINICAL MONITORING OF PATEINTS ON CLOZAPINE - Gul, M.; Nihgam, A; Broughton , N (Journal of Pakistan Psychiatric Society, 2006)
Objective: To find out if the Maudsley Guidelines for clinical monitoring of the patients on Clozapine has been followed or not and association of Clozapine with Diabetes Mellitus and Hyperlipidemia. Design: Descriptive observational study. Place & Duration of Study: Study was carried out at Three Bridges Unit Ealing Hospital West London Mental Health NHS Trust London .The data was collected between Dec 2005 & Jan 2006. Subjects & Methods: Study includes all the in-patient at the time of Data Collection started on Clozapine since Sept 1999.Pateints details were obtained from Clozapine Clinic at Three Bridges Unit Ealing Hospital .Data was collected by looking at patient’s blood results retrospectively via an access to Central Path Lab Data system at Ealing Hospital. Results: The total number of patients was 60 out of which 52 were males and 8 were females. 3.33% of the sample was less than 25 years old, 45% were between 25-40, 48.3% were between 40-60 and 3.33% were above 60 years of age. There were 41.67% white British, 13.33% Black British, 10% British Asians while the rest 35% were of miscellaneous ethnic origin. The results signify the importance of following the Maudsley guide lines in clinical monitoring of patients on Clozapine. It also supports the previous established studies of association of Clozapine with Hyperglycemia1 . Conclusion: All patients receiving Clozapine should be regular monitored for changes in weight, lipid, and glucose levels so that appropriate preventive and therapeutic measures can be initiated. Key words: Clinical monitoring, Clozapine, Diabetes mellitus, Hyperlipidemia.